Occupational mobility and gender: implications for government policy - Robbins, Donald (Estudios de Economía, 2016)
Data on all persons employed in the California State Civil Service between 1977 and 1985 reveals a marked improvement in the distribution of women across income classes. An important part of this improvement appears due to internal mobility. Survival function estimates show that upward mobility was high for employees starting in female-dominated occupations, absolutely and compared to mobility out of male-dominated, manual occupations. Hazard rate estimates show that mobility was increased by longer leaves and moving to full-time status and decreased by the number of separations. The effectiveness of occupational classifications designed to aid mobility was ambiguous.